Selective Extrapontine Myelinolysis in Osmotic Demyelination Syndrome in a Case of Previously Undiagnosed Sheehan’s Syndrome with Recurrent Hyponatraemia - A Rare Association - Siddiqui, FM; Siddiqui, Md Mahmudur Rahman; Hoque, Md Azharul; Shujon, Saeedur Rahman; Hossain, Ahmed (Journal of Medicine, 2011)
Selective extrapontine myelinolysis (EPM) following a marked change in osmolarity, usually due to the rapid correction of hyponatraemia. Association of EPM in hyponatraemia from Sheehan's syndrome is very rare. We report a 38 years old lady with EPM, who presented with repeated attacks of hyponatraemia for 2 years, which were corrected several times after hospital admissions. She has got history of postpartum haemorrhage about 10 years back followed by secondary amenorrhoea and lactational failure. At present she came to us with features of parkinsonism, dystonia, mutism, insomnia and emotional outburst. Her magnetic resonance imaging (MRI) of the brain revealed features of myelinolysis with atrophied pituitary gland. Her serum pituitary hormonal levels confirm presence of hypopituitarism with secondary adrenal failure due to Sheehan's syndrome. Now her present features are due to selective extrapontine myelinolysis of osmotic demyelination, might be due to any episode of inappropriate intravenous correction of hyponatraemia. Keyword: Sheehan's syndrome; Hyponatraemia; Extrapontine myelinolysis; Osmotic demyelination syndrome DOI: 10.3329/jom.v12i1.6936 J Medicine 2011; 12 : 77-80